Adding Standardized Transcriptions to Panoan and Tacanan Languages in the Intercontinental Dictionary Series (Computer-Assisted Language Comparison in Practice: Tutorials on Computational Approaches to the History and Diversity of Languages, 2024)
In this study, we illustrate how standardized phonetic transcriptions can be added to the data for Panoan and Tacanan languages provided by the Intercontinental Dictionary Series. The result is presented as a new dataset that keeps reference to the original data and adds phonetic transcriptions for each word form in Panoan languages, Tacanan languages, as well as Spanish and Portuguese.
Keywords: Panoan languages; Tacanan languages; CLDF datasets; comparative wordlist; Intercontinental Dictionary Series